Field Validation of a Mob Composite Sampling Protocol to Estimate Herd Parasitism in Cattle - Ashlee Gibbons (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: Evaluate the efficacy of a mob composite sampling (MOB) approach against the existing industry standard fecal sampling protocol of individual samples (IDV) to determine herd fecal egg counts of nematodes in beef cattle. Study Description: Samples (n = 1,060) from fresh pen floor fecal pats were collected at random from cattle (calf-fed and yearling) in commercial feedlots (n = 12) and sale barns (n = 1). Sample sets of 20 fecal pat samples were collected by pen (n = 53), ranging from 64 to 225 animals. The MOB samples (n = 106) were further processed to yield two composite samples, each representing 10 of the original pen samples. The IDV and MOB samples were analyzed by microscope for nematode eggs/3 g. The Bottom Line: Results indicate a mob sampling approach using two composite samples each representing 10 fecal pats, can determine parasite loads with 91.7% confidence in received cattle relative to industry standard field fecal sampling techniques.
Keywords: cattle; fecal egg count; parasite